ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIK SISWA SMP PADA MATERI PERSAMAAN LINEAR SATU VARIABEL - Endang Siti Novianti; Luvy Sylviana Zanthy (Departement of Mathematics Education, 2019)
This study aims to analyze the level of mathematical problem solving ability of junior high school students in Cianjur Regency on one variable linear equation material. The method used in this study is qualitative descriptive method. The population in this study were seventh grade students in one of the junior high schools in Cianjur Regency which numbered 50 students. The sampling technique is by purposive sampling technique, then 10 research subjects were determined. The instrument used was in the form of 4 items about mathematical problem solving abilities in one variable linear equation material and interviews on selected subjects. The conclusion of this study is the mathematical problem solving ability of seventh grade students in Cianjur Regency seen from the indicators identifying the adequacy of the data to solve the problem is quite high, but the indicators make mathematical models, apply strategies to solve problems and check the truth of the results and answers are still relatively low